Turbulence and anomalous tokamak transport control by Geodesic Acoustic Mode. (26th June 2015) - Gurchenko, A. D.; Gusakov, E. Z.; Niskala, P.; Altukhov, A. B.; Esipov, L. A.; Kiviniemi, T. P.; Kouprienko, D. V.; Kantor, M. Yu.; Lashkul, S. I.; Leerink, S.; Perevalov, A. A.; Korpilo, T.
Abstract: The elementary process of turbulence control by Geodesic Acoustic Modes (GAMs) leading to modulation of its level at the GAM frequency is for the first time supported by experimental observations at the FT-2 tokamak. The modulation effect is confirmed by the global total-distribution-function gyrokinetic modelling of the tokamak discharge, predicting strong modulation of the electron thermal diffusivity induced by GAMs, which propagates inward and possesses the GAM temporal and spatial structure.